2012
DOI: 10.1007/s11356-011-0735-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bactericidal efficacy of silver ions on Escherichia coli for drinking water disinfection

Abstract: The findings of this study revealed that very low concentrations of silver ions at pH 8-9 and temperature >20°C have bactericidal efficacy for total disinfection of drinking water. Silver ionisation is suitable for water disinfection and an appropriate alternative to chlorination which forms carcinogenic disinfection by-products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…24 Another antimicrobial approach that has shown significant potential is the use of metals, mainly silver. 25 Silver ions have been added to bone cement demonstrating antibacterial action without impinging on the cytotoxicity of the biomaterial. 26,27 Silver nanoparticles, sometimes called colloidal silver or metal silver, have also proved an effective antimicrobial agent and they have been encapsulated in many medical devices to confer these antimicrobial properties to bandages, 28 sutures, 29 surgical scrubs, 30 and catheters.…”
Section: Introductionmentioning
confidence: 99%
“…24 Another antimicrobial approach that has shown significant potential is the use of metals, mainly silver. 25 Silver ions have been added to bone cement demonstrating antibacterial action without impinging on the cytotoxicity of the biomaterial. 26,27 Silver nanoparticles, sometimes called colloidal silver or metal silver, have also proved an effective antimicrobial agent and they have been encapsulated in many medical devices to confer these antimicrobial properties to bandages, 28 sutures, 29 surgical scrubs, 30 and catheters.…”
Section: Introductionmentioning
confidence: 99%
“…On account of these uses and their possibly toxic effects in human and aquatic organisms, the determination of silver nanoparticles in water samples can be also considered of great interest in the aquatic field [8][9][10][11][12]. Due to their bactericidal properties, silver salts and silver nanoparticles are used in disinfection of drinking water [13][14][15]. Therefore, silver can be used as a tracer for monitoring domestic and industrial inputs [16] being of great interest the analysis of this ion in water samples.…”
mentioning
confidence: 99%
“…A 4 log reduction (approximately) was seen at 100µg/l after 24 hours of exposure. Pathak and Gopal (2012) evaluated the efficacy of silver ions against E. coli. Bacteria (concentration -1.75 x 10 3 cfu/ml) were exposed to various concentrations of silver ions (1, 2, 5, 10 and 20 µg/l), produced from silver electrodes, for up to 60 minutes.…”
Section: Water Disinfection Efficacymentioning
confidence: 99%
“…Generally, relatively long contact times were required to effectively reduce bacterial concentrations (e.g. 3 hours or longer), the exception being the study of Pathak and Gopal (2012) where silver ions were generated electrolytically (rather than from silver salts), and complete inactivation (3 log) was seen after 20 minutes at a relatively low silver concentration (20µg/l). In contrast to the lab spiked samples, where generally good log reductions were reported, relatively poor results (lower log reductions) were seen in harvested rainwater samples (low initial bacterial concentration) used by Nawaz et al (2012) and they suggested that this may result from greater resistance to disinfection in microbes grown in low nutrient systems.…”
Section: Water Disinfection Efficacymentioning
confidence: 99%